Allozyme variation between European and New Zealand populations of Microctonus aethiopoides - Iline, I.I.; Phillips, C.B. (New Zealand Plant Protection, 2003)
The parasitoid Microctonus aethiopoides Loan (Hymenoptera Braconidae) was introduced to New Zealand in 1982 for control of Sitona weevil Sitona discoideus Gyllenhal (Coleoptera Circulionidae) a pest of lucerne Unfortunately New Zealand populations of M aethiopoides do not parasitise clover root weevil Sitona lepidus Gyllenhal but European populations do Several PCRbased methods have demonstrated the existence of genetic variation between and amongst European and New Zealand populations of M aethiopoides However enzyme electrophoresis methods have the potential to provide less expensive population markers and these could also prove more useful than PCRbased markers for studying gene flow between European and New Zealand M aethiopoides populations This paper reports a preliminary assessment of allozyme variation between European and New Zealand M aethiopoides Nine enzymes and general proteins were assayed but the only variation was observed at esterase (EST) with two alleles present at each of two loci